Análisis de flujos de inundación en la cuenca del río Papagayo, Guerrero - Reyes Soto, Fernando (My University, 2014)
Análisis de flujos de inundación en la cuenca del río Papagayo, Guerrero
Keywords: Análisis de flujos de inundación en la cuenca del río Papagayo, Guerrero